Pengembangan Kecerdasan Emosional dalam Membangun Kedamaian di Sekolah - Iswati Iswati; Dewi Maharani; Arief Budiarto (Pancanaka, 2021)
The purpose this study was analyze the development of emotional intelligence to build peace at school. This research using the literature study method. Ideally, school is safe and comfortable place for students to get academic, moral, ethical education, and even become a second home for students. However, various acts of violence and deviant behavior are still often found in schools. Based on the phenomena that occur in the educational environment, it can be seen that school is not a safe and comfortable place for students. The existence acts of violence either directly or indirectly have an impact on the physical and psychological health of students. Therefore, the development of emotional intelligence is an important thing in schools. Emotional intelligence is an ability, capacity, or skill possessed by students to identify, assess, and manage emotions in themselves, others, and groups. By developing emotional intelligence, students have empathy, care, and tolerance towards others, so students can use their emotions well.